Pengembangan Media Video Pembelajaran Mendesain Busana Secara Manual Bagi Siswa Kelas XI Busana di SMKN 1 Lembah Gumanti - Maharani, Anjelina; Ernawati, Ernawati; Efi, Agusti; Suci, Puji Hujria (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Traditional learning methods need to be complemented with instructional media that can serve as a reference for students in the design process. Based on learning outcome data at SMK Negeri 1 Lembah Gumanti, Class XI Fashion Design, more than 60% of students have not yet achieved the Minimum Mastery Criteria (KKM) in the manual fashion design competency. This study is a development research that aims to produce an instructional video for manual fashion design that is valid and practical for use by Class XI Fashion Design students at SMK Negeri 1 Lembah Gumanti. The result model employed is the Alessi and Trollip model, which consists of three main stages: planning, design, and development. The results of the media validation obtained a score of 84.5%, and the material validation obtained a score of 89.8%, both categorized as very valid. The practicality test by teachers achieved a score of 93.7%, the small-scale trial 95%, and the large-scale trial 91.5%, all categorized as very practical. Based on these results, the developed instructional video media is declared highly valid and practical for use in the Fashion Expertise Concentration subject at vocational high schools.